2014
DOI: 10.1148/radiol.13130101
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Diversity by Race, Hispanic Ethnicity, and Sex in Diagnostic Radiology

Abstract: Females and URM remain underrepresented in the diagnostic radiology physician workforce despite an available medical student pipeline. Given prevalent health care disparities and an increasingly diverse society, future research and training efforts should address increasing resident diversity with program directors and department chairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(70 citation statements)
references
References 35 publications
7
63
0
Order By: Relevance
“…A 2014 study found that the percentages of female practicing radiologists (23.5%), academic radiology faculty (26.1%), radiology residents (27.8%), and radiology applicants (28.1%) were all substantially below the percentage of women graduating from medical school in the United States (48.3%) [2]. Additionally, of the twenty largest residency training programs in the US, radiology ranked ninth for overall size but only seventeenth for female representation [2].…”
Section: The Problem: Too Few Female Role Models In Radiologymentioning
confidence: 99%
See 4 more Smart Citations
“…A 2014 study found that the percentages of female practicing radiologists (23.5%), academic radiology faculty (26.1%), radiology residents (27.8%), and radiology applicants (28.1%) were all substantially below the percentage of women graduating from medical school in the United States (48.3%) [2]. Additionally, of the twenty largest residency training programs in the US, radiology ranked ninth for overall size but only seventeenth for female representation [2].…”
Section: The Problem: Too Few Female Role Models In Radiologymentioning
confidence: 99%
“…Over the last four decades, the percentage of female radiologists in the United States has held steady in the low to mid-20s [2,3,4,5]. Many studies have been conducted in recent years to better understand the forces behind the apparent gendering of certain medical specialties, a term which reflects the overwhelming predominance of women in some specialties such as pediatrics and obstetrics-gynecology and men in others such as radiology and orthopedic surgery [6,7,8].…”
Section: The Problem: Too Few Female Role Models In Radiologymentioning
confidence: 99%
See 3 more Smart Citations